Aging and old age in the opinion of high school students in Chojnice - Topczewska, Katarzyna; Stangret, Anna; Mularczyk, Agata; Szczęśniak, Angelika; Rogulska, Karolina; Kapczuk, Patrycja (Journal of Education, Health and Sport, 2020)
Nowadays, a significant increase in the number of post-working age people can be observed. This is due primarily to the change of life style, taking care of their own health and the development of medicine. Therefore, the perception of old people and their problems have become a common theme and subject of research. Aging and old age are referred to as the next stage in human development, which puts it in front of an extremely severe challenges or difficulties. The aim of this study was to present the views of High School students about aging and old age. In the anonymous and voluntary survey involved 252 students in grades first Chojnice High Schools. The author's questionnaire was used, containing 26 questions. Analyzes were performed using IBM SPSS version 24 and Microsoft Office Excel. In our own research, the relationship between the gender of respondents and the fear of old age was proved, which shows that women are more likely to fear their own old age. The correlation between place of residence and opinion on the need for elderly people in society was also examined. It was shown that among the youth living in the city up to 100,000 inhabitants were people who thought that the old people were unnecessary for the society. However, the vast majority of opinion-makers declared the need for old people in the population. The results of the study showed that young people have a positive attitude to the older generation. There was no stereotypical perception of old people by young people.